Conflict Changes How People View God - Caluori, Nava; Jackson, Joshua Conrad; Gray, Kurt; Gelfand, Michele (Psychological Science, 2020)
Religion shapes the nature of intergroup conflict, but conflict may also shape religion. Here, we report four multimethod studies that reveal the impact of conflict on religious belief: The threat of warfare and intergroup tensions increase the psychological need for order and obedience to rules, which leads people to view God as more punitive. Studies 1 ( N = 372) and 2 ( N = 911) showed that people’s concern about conflict correlates with belief in a punitive God. Study 3 ( N = 1,065) found that experimentally increasing the salience of conflict increases people’s perceptions of the importance of a punitive God, and this effect is mediated by people’s support for a tightly regulated society. Study 4 showed that the severity of warfare predicted and preceded worldwide fluctuations in punitive-God belief between 1800 CE and 2000 CE. Our findings illustrate how conflict can change the nature of religious belief and add to a growing literature showing how cultural ecologies shape psychology.